Developing An Instructional Design for Writing A Product Knowledge by Fusing Multimodality Approach and Industry Practitioner Teaching Practice - Wigati, Fikri Asih Asih (Universitas Riau, 2024)
There is a research aim in this study: create an instructional design by incorporating the Teaching Practitioner program and the Multimodality approach which focus on one learning outcome: composing a product knowledge of manufacturing industry. An instructional design was developed utilizing the Dick and Carey Model, involving some developments steps. The instructional design developed for this study combined elements of the Teaching Practitioner and the Multimodality approach with the English lecturer and the practitioner playing significant roles in each phase; and the implemented instructional design was able to enhance students' writing proficiency as demonstrated by the writing results. Based on the favorable results observed in this study regarding the implementation of the instructional design, the researcher proposes that ESP courses can adopt the identical instructional design.